Prehispanic underground drainage system - Ardiles Nieves, Percy E. (1986)
Various written sources and archaeological studies carried out in the Sierra and Costa indicate that in these regions the use and management of soil and water in pre-Hispanic Peru predated the Incas (Guamán Poma de Ayala 1936: 54-62; Avila 1975: 129f. ). However, the extensive network of hydraulic systems built by the Incas in the Tahuantinsuyo allows us to support that they were not only heirs or repositories of the technology of their predecessors the Mochicas, Chimús and/or Nazcas, but also managed to surpass them in handling , organization and distribution of its water resources.